How Many Microwave Disinfection Cycles is Safe for the Adaptability of Polymethyl Methacrylate (PMMA) Denture Base Materials?: An In Vitro Study - Wan Nor Syariza Wan Ali; Noor Farishahbanubinti Ahmad; Sharifah Nor Aishah Syed Yussof (Wolters Kluwer Medknow Publications, 2022)
Introduction: We aimed to determine the maximum microwave disinfection cycles that is safe for the adaptability of polymethyl methacrylate (PMMA) denture bases under power-time setting of 630 W for 3 minutes. Materials and Methods: Thirty PMMA maxillary denture bases were constructed and divided into two groups, control (no disinfection) and test (microwave disinfection at 630W for 3 minutes in water immersion). Coltene Rapid Liner (Coltene/Whaledent AG, Altstatten, Switzerland) silicone was coated onto the internal surface of the samples followed by placement of 8 kgf of axial load. The silicone film was removed, and weighed using analytical balance. One day interval was given between each cycle and samples were stored in 37°C water bath. Tests were carried out until a statistically significant silicone film weight change detected. The data were analyzed on SPSS version 21.0 (IBM Corp, Armonk, NY). Results: Statistically significant change of the denture base was detected after the tenth cycle of microwave irradiation. Conclusion: The maximum microwave disinfection cycles that is safe for the adaptability of PMMA denture bases under power-time setting of 630 W for 3 minutes is only up to 10 cycles.